Analysis of the Influence of 7P Marketing Mix on Customer Satisfaction and Loyalty: A Case Study of Nanda Gift & Souvenir Shop - Ananda, Dwi Shinta; Ratnasari, Vita (Publikasi Indonesia, 2025)
In the midst of increasingly fierce market competition, Nanda Gift & Souvenir Shop, as a provider of a wide range of gift products for various events, faced the challenge of increasing customer satisfaction and loyalty. The background of this problem arises from the level of customer satisfaction that is not optimal, which then has an impact on the low level of loyalty and the frequency of purchases of regular customers. This study aims to identify the factors that affect customer satisfaction at Nanda Gift & Souvenir Shop and evaluate the effectiveness of using Marketing Mix 7P to strengthen customer loyalty. The analysis was carried out by quantitative method through the distribution of questionnaires with 202 respondents, then analyzed using Structural Equation Modeling Partial Least Square (SEM-PLS). Based on the results of SEM-PLS analysis, it was found that the factors of product, price, place, promotion, labor, process, and physical evidence have a significant influence on customer satisfaction. The labor factor has the most dominant influence, followed by product, promotion, and physical evidence. Furthermore, the results of the study show that customer satisfaction has a significant and positive influence on customer loyalty. Customers who are satisfied with the products and services they receive tend to have higher levels of loyalty.